TAṢMĪM TA’LĪM AL-LUGAH AL-‘ARABIYYAH AL-MUTTAJIH ILA MAHĀRĀT AL-TAFKĪR AL-ULYA FI ḌAUI AL-MADKHAL AL-LUGAWI AL-KULLI FI MADRASAH AL-MUTAWASSIṬAH AL-ISLAMIYYAH AL-HUKUMIYAH 2 MAGETAN JAWA AL-SYARQIYYAH - Ahmad Royani; Niken Nur Hanifah; Muhbib Abdul Wahab muhbib (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research based on the phenomenon of the implementation of higher order thinking skills in Arabic language learning which is characterized by memorizing linguistic knowledge and recognizing language symbols, in fact it can grow if students are facilitated to understanding and reasoning the knowledge as a basis for applying, analyzing, evaluating and creating. Therefore developing the Arabic language teaching design based on high order thinking skill with a learning model that can accommodate the learning of language skills is indispensable. This research use the research and development method, and the datas collection method is observation, questionnare, test and documentation. The results of the study are innovation of developing Arabic teaching design based on high order thinking skill with whole language model which includes several stages material analysis, basic competency analysis, indicators analysis, formulating learning objectives, developing model, strategies and learning activities, developing learning materials, tools, assessments, linking the principles of HOTS. The study result indicate that the Arabic teaching design meets the effective criteria seen from the N-Gain score 0,72 with a good criteria, as for the average of all validation instruments 92,54% with a very good category, and the average of observation of 74,2% were practical.